Splenogonadal fusion - Namita Bhutani; Pradeep Kajal; Vijender Sangwan (Journal of Pediatric Surgery Case Reports, 2020)
Splenogonadal fusion (SGF) is a rare congenital anomaly which is characterized by congenital fusion between the spleen and testicular tissue. Literature highlights approximately 175 reported cases, and most of these are associated with cryptorchidism. This congenital malformation may occur due to the proximity of developing gonad and spleen, resulting in abnormal connection between them during gestation. It may be an incidental finding on ultrasonography and during orchiopexy or inguinal hernioplasty or less frequently it can present as a scrotal swelling mimicking a testicular tumor. We, hereby, present a case of 12-year-old male patient with swelling in the left scrotum for 8 months. Scrotal exploration with excision of the ectopic tissue was done. Histopathology showed it to be ectopic splenic tissue surrounding testicular parenchyma suggestive of SGF. Its diagnosis is challenging for clinicians and it's rarely suspected and diagnosed preoperatively. However, recent imaging methods can aid in the diagnosis. Despite its indolence, diagnosis is often confirmed after orchidectomy. Surgery is mandatory, to rule out the rare association with malignancy. A better knowledge of the clinical and radiological features of SGF provides an opportunity for conservative surgery. SGF as a rare cause of testicular swelling should be kept in mind and evaluated to avoid unnecessary orchidectomy.